Biomarkers of memory variability in traumatic brain injury. Issue 1 (15th December 2020) - Adamovich-Zeitlin, Richard; Wanda, Paul A; Solomon, Ethan; Phan, Tung; Lega, Bradley; Jobst, Barbara C; Gross, Robert E; Ding, Kan; Diaz-Arrastia, Ramon; Kahana, Michael J
Abstract: Traumatic brain injury is a leading cause of cognitive disability and is often associated with significant impairment in episodic memory. In traumatic brain injury survivors, as in healthy controls, there is marked variability between individuals in memory ability. Using recordings from indwelling electrodes, we characterized and compared the oscillatory biomarkers of mnemonic variability in two cohorts of epilepsy patients: a group with a history of moderate-to-severe traumatic brain injury ( n  = 37) and a group of controls without traumatic brain injury ( n  = 111) closely matched for demographics and electrode coverage. Analysis of these recordings demonstrated that increased high-frequency power and decreased theta power across a broad set of brain regions mark periods of successful memory formation in both groups. As features in a logistic-regression classifier, spectral power biomarkers effectively predicted recall probability, with little difference between traumatic brain injury patients and controls. The two groups also displayed similar patterns of theta-frequency connectivity during successful encoding periods. These biomarkers of successful memory, highly conserved between traumatic brain injury patients and controls, could serve as the basis for novel therapies that target disordered memory across diverse forms of neurological disease. Abstract : Traumatic brain injury (TBI) is a leading cause of cognitive disability and often associated with episodic memory impairment. Adamovich-Zeitlin et al. reveal that neural biomarkers of variable mnemonic function (see figure) appear highly conserved in epileptic patients with and without significant TBI history, which may guide future neuromodulatory therapies. Graphical Abstract: